Quality control - Besterfield, Dale H. (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2009)
'Quality Control, Eighth Edition takes a practical approach to providing a fundamental yet comprehensive coverage of statistical quality control concepts. This text presents readers with a sufficient amount of theory to ensure a sound understanding of the basic principles of quality control. Probability and statistical techniques are presented through the use of simple mathematics, as well as with tables and charts.''This text is designed to be used in an introductory course in the quality field. It provides the prerequisite foundation necessary for an advanced course in experimental design.'--Back Cover.
1: Introduction To Quality -- Objectives -- Introduction -- Responsibility for quality -- Chief executive officer -- Computers and quality control -- 2: Total Quality Management-Principles And Practices -- Objectives -- Introduction -- Basic approach -- Leadership -- Customer satisfaction -- Employee involvement -- Continuous process improvement -- Supplier partnership -- Performance measures -- Deming's 14 points -- Final comments -- 3: Total Quality Management-Tools And Techniques -- Objectives -- Introduction -- Statistical process control -- Acceptance sampling -- Reliability -- Design of experiments -- Taguchi's quality engineering -- Failure mode and effect analysis -- Quality function deployment -- ISO 9000 -- ISO 14000 -- Benchmarking -- Total productive maintenance -- Management and planning tools -- Quality by design -- Products liability -- Information technology -- Lean -- Computer program -- 4: Fundamentals Of Statistics -- Objectives -- Introduction -- Frequency distribution -- Measures of central tendency -- Measures of dispersion -- Other measures -- Concept of a population and a sample -- Normal curve -- Tests for normality -- Scatter diagram -- Computer program -- 5: Control Charts For Variables -- Objectives -- Introduction -- Control chart techniques -- State of control -- Specifications -- Process capability -- Six Sigma -- Other control charts -- Computer program -- 6: Additional SPC Techniques For Variables -- Objectives -- Introduction -- Continuous and batch processes -- Multi-Vari Chart -- Short-Run SPC -- Gage control -- Computer program -- 7: Fundamentals Of Probability -- Objectives -- Introduction -- Basic concepts -- Discrete probability distributions -- Continuous probability distributions -- Distribution interrelationship -- Computer program -- 8: Control Charts For Attributes -- Objectives -- Introduction -- Control charts for nonconforming units -- Control charts for count of nonconformities -- Quality rating system -- Computer program -- 9: Lot-By-Lot Acceptance Sampling By Attributes -- Objectives -- Introduction -- Fundamental concepts -- Statistical aspects -- Sampling plan design -- Computer program -- 10: Acceptance Sampling Systems -- Objectives -- Introduction -- Lot-by-lot acceptance sampling plans for attributes -- Acceptance sampling plans for continuous production -- Acceptance sampling plans for variables -- 11: Reliability -- Objectives -- Introduction -- Fundamental aspects -- Additional statistical aspects -- Life and reliability testing plans -- Test design -- Availability and maintainability -- Computer program -- 12: Management And Planning Tools -- Objectives -- Introduction -- Why, why -- Forced field analysis -- Nominal group technique -- Affinity diagram -- Interrelationship diagram -- Tree diagram -- Matrix diagram -- Prioritization matrices -- Process decision program chart -- Activity network diagram -- Summary -- Appendix -- Table A: Areas under the normal curve -- Table B: Factors for computing central lines and 3 control limits for X, s, and R charts -- Table C: Poisson distribution -- Table D: Random numbers -- Table E: Commonly used conversion factors -- Selected bibliography -- Glossary -- Answers to selected exercises -- Index.
Book is accompanied by one computer optical disc entitle'Quality control' Bearing the same call number and available at PL2
Includes bibliographical references (pages 523-525) and index.
Keywords: Quality control